Comparative Genomics and Transcriptomics Depict Marine Algicolous Arthrinium Species as Endosymbionts That Help Regulate Oxidative Stress in Brown Algae - Heo, Young Mok; Oh, Seung-Yoon; Kim, Kyeongwon; Han, Sang-Il; Kwon, Sun Lul; Yoo, Yeonjae; Kim, Dongjun; Khim, Jong Seong; Kang, Seunghyun; Lee, Hanbyul; Kim, Jae-Jin (Frontiers in Marine Science, 2021)
The whole genome and transcriptome analyses were performed for prediction of the ecological characteristics of Arthrinium and the genes involved in gentisyl alcohol biosynthesis. Whole genome sequences of A. koreanum KUC21332 and A. saccharicola KUC21221 were analyzed, and the genes involved in interspecies interaction, carbohydrate-active enzymes, and secondary metabolites were investigated. Three of the seven genes associated with interspecies interactions shared by four Arthrinium spp. were involved in pathogenesis. A. koreanum and A. saccharicola exhibit the enzyme profiles similar to those observed in plant pathogens and endophytes rather than saprobes. Furthermore, six of the seven metabolites of known clusters identified in the genomes of the four Arthrinium spp. are associated with plant virulence. These results indicate that Arthrinium spp. are potentially pathogenic to plants. Subsequently, different conditions for gentisyl alcohol production in A. koreanum were established, and mRNA extracted from cultures of each condition was subjected to RNA-Seq to analyze the differentially-expressed genes. The gentisyl alcohol biosynthetic pathway and related biosynthetic gene clusters were identified, and gentisyl alcohol biosynthesis was significantly downregulated in the mannitol-supplemented group where remarkably low antioxidant activity was observed. These results indicate that gentisyl alcohol production in algicolous Arthrinium spp. is influenced by mannitol. It was suggested that the algicolous Arthrinium spp. form a symbiotic relationship that provides antioxidants when the photosynthetic activity of brown algae decreases in exchange for receiving mannitol. This is the first study to analyze the lifestyle of marine algicolous Arthrinium spp. at the molecular level and suggests a symbiotic mechanism with brown algae. It also improves the understanding of fungal secondary metabolite production via identification of the gentisyl alcohol biosynthetic gene clusters in Arthrinium spp.